Oral health and healthcare utilization in Belgian dentate adults. Issue 5 (31st July 2019) - Bottenberg, Peter; Vanobbergen, Jacques; Declerck, Dominique; Carvalho, Joana C.
Abstract: Objectives: In 2012‐2014, the Belgian National Oral Health Data Registration and Evaluation Survey, integrated in the Health Interview Survey (HIS), was carried out. The present study investigated, in a sample of 1340 dentate adults (≥25 years), the association between oral healthcare utilization, oral health status and sociodemographic status. Methods: A multistage, stratified cluster sampling procedure was used. Oral examination for caries experience (World Health Organization, D3 MFT‐Index), periodontal status (Dutch Periodontal Screening Index, DPS‐Index), number of teeth present and occlusal contacts without wearing removable dentures was performed by calibrated examiners. Oral healthcare utilization data were retrieved from the records of the Belgian Intermutualistic Agency. Participants' oral health and sociodemographic data were linked to registered oral care utilization in the previous 5‐year period. Regular attenders (annual attenders and those with at least one registered contact in three different years) were compared with irregular attenders (those having had dental visits but not according to the definition of regular attenders) and nonattenders. Data were weighted to compensate for sampling and participation bias. Results: Six hundred and seventy‐nine participants attended regularly, of whom 276 annually; 256 did not attend in the reference period. The overall D3 MFT‐Index was not noticeably different between attendance patterns (varying between 11 and 13), although regular attenders had more restored teeth than nonattenders ( P < 0.01). No difference was seen for DPS‐Index and number of teeth/occluding pairs ( χ 2 test, P > 0.05). Females, participants with higher education, older participants and those in employment had higher rates of regular attendance. Conclusions: Regular attenders had fewer untreated caries lesions, but neither lower caries experience nor lower DPS‐Index than irregular attenders. Regular attendance was associated with sociodemographic variables.